Climate Variability and peasant agriculture in Kélo in the south of Chad - Mfewou, Abdoulay; Tata, Julius; Nadji, Paul (Advances in Social Sciences Research Journal, 2020)
With its Sahelian climate, Chad presents climatic parameters which have a very negative impact on its agricultural productivity. Faced with this natural problem for peasant society, political decision-makers do little to support local adaptation mechanisms. The study in Kélo, southern Chad, (606.9 mm; 28.9 ° C) was carried out for five months. The survey was conducted with 140 heads of households randomly chosen from this area to collect information relating to the damage caused by climatic vagaries on the yields of cultivated plants and the analysis of meteorological data collected at the Kélo station by l 'Chad Institute of Agronomic Research for Development (ITRAD) on climate variability which shows the irregularities of the rains at their beginnings and / or at their ends, the shortening of the rainy season and, a slight rise in temperature. These rainfall irregularities, the main crops are experiencing yield reductions of the order of 70¨% of the average, approximately: 20-25 bags of paddy per hectare against 7-12 bags of paddy for rice, 4-5 bags / ha against 2-3 bags / ha for sorghum and pearl millet, 10-13 bags / ha against 6-9 bags / ha for peanuts, 600-900 kg / ha against 250-600 kg for cotton, etc. . In 2018, rainfall over time shows linear correlations established between cereal and cotton yields on the one hand, and those of annual rainfall on the other. The result also shows that there are no explicit linear relationships between these variables. This shows that, mere knowledge of the rainfall regime is not enough to explain the decline in agricultural production; because poor agricultural production can result from both poor and surplus water conditions and / or poor distribution of rains. It is recorded that food production per capita also decreases; this decline occupies a very important place in all policies of local development projects but weakly applied by rural decision-makers. Consequently, there is recurrent food insecurity, putting the farmer in a dependency on assistantship from outside the region.